2014
DOI: 10.1371/journal.pone.0084853
|View full text |Cite
|
Sign up to set email alerts
|

Engineering the Saccharomyces cerevisiae β-Oxidation Pathway to Increase Medium Chain Fatty Acid Production as Potential Biofuel

Abstract: Fatty acid-derived biofuels and biochemicals can be produced in microbes using β-oxidation pathway engineering. In this study, the β-oxidation pathway of Saccharomyces cerevisiae was engineered to accumulate a higher ratio of medium chain fatty acids (MCFAs) when cells were grown on fatty acid-rich feedstock. For this purpose, the haploid deletion strain Δpox1 was obtained, in which the sole acyl-CoA oxidase encoded by POX1 was deleted. Next, the POX2 gene from Yarrowia lipolytica, which encodes an acyl-CoA ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
47
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 39 publications
(51 citation statements)
references
References 31 publications
4
47
0
Order By: Relevance
“…In comparison with control rats, hypoxanthine was obviously down‐regulated in diet‐induced hyperlipidemic rats, which was consistent with a previous study (Jiang et al, , b). Our previous study showed that 3‐methyluridine is a biomarker in rats with hyperlipidemia and 3‐methyluridine was restored after treatment with rhubarb (Chen et al, , b, c). In addition, 3‐methyluridine is associated with fat mass and obesity‐associated gene and RNA modification analyses uncovered that loss of fat mass and obesity gene affects the 3‐methyluridine/uridine and pseudouridine/uridine ratios in total brain RNA (Berulava et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In comparison with control rats, hypoxanthine was obviously down‐regulated in diet‐induced hyperlipidemic rats, which was consistent with a previous study (Jiang et al, , b). Our previous study showed that 3‐methyluridine is a biomarker in rats with hyperlipidemia and 3‐methyluridine was restored after treatment with rhubarb (Chen et al, , b, c). In addition, 3‐methyluridine is associated with fat mass and obesity‐associated gene and RNA modification analyses uncovered that loss of fat mass and obesity gene affects the 3‐methyluridine/uridine and pseudouridine/uridine ratios in total brain RNA (Berulava et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, propionylcarnitine, methylhippuric acid, 4‐aminohippuric acid, hippuric acid and phenylacetylglycine were involved in fatty acid metabolism of RA‐treated hyperlipidemic rats. Compared with the control group, urinary hippuric acid and methylhippuric acid in diet‐induced hyperlipidemic group were higher, which was recognized as a possible sign of atherosclerosis (Zhang et al, , b; Chen et al, , b, c). However, after oral administration of RA, their abnormalities were restored to normal.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Peroxisomes have recently been used to enhance the microbial production of biofuels . While many long chain organic acids can be produced by commonly used microorganisms such as Saccharomyces cerevisiae , medium chain organic acids are preferred for use as biofuels .…”
Section: Pathway Compartmentalization In Peroxisomesmentioning
confidence: 99%